Natural Mosquito-Pathogen Hybrid IgG4 Antibodies in Vector-Borne Diseases: A Hypothesis - Londono-Renteria, Berlin; Cardenas, Jenny C.; Troupin, Andrea; Colpitts, Tonya M. (Frontiers in Immunology, 2016)
Chronic exposure to antigens may favor the production of IgG4 antibodies over other antibody types. Recent studies have shown that up to a 30% of normal human IgG4 is bi-specific and is able to recognize two antigens of different nature. A requirement for this specificity is the presence of both eliciting antigens in the same time and at the same place where the immune response is induced. During transmission of most vector-borne diseases, the pathogen is delivered to the vertebrate host along with the arthropod saliva during blood feeding and previous studies have shown the existence of IgG4 antibodies against mosquito salivary allergens. However, there is very little ongoing research or information available regarding IgG4 bi-specificity with regards to infectious disease, particularly during immune responses to vector-borne diseases such as malaria, filariasis or dengue virus infection. Here, we provide background information and present our hypothesis that IgG4 may not only be a useful tool to measure exposure to infected mosquito bites, but that these bi-specific antibodies may also play an important role in modulation of the immune response against malaria and other vector-borne diseases in endemic settings.